Menggagas Kurikulum Pendidikan Agama Islam Berbasis Multikultur dan Pluralisme - Muhibuddin; Hamdani; Tajul Munir (Program Studi Pendidikan Agama Islam, 2024)
ABSTRACT (Inggris) This research discusses the importance of developing multicultural and pluralistic curricula in Islamic religious education to address challenges in today's ethnically, culturally, and religiously diverse society. Using a qualitative methodology with a literature-based approach, the study emphasizes education's vital role in character formation, particularly in building tolerance and coexistence among different religious adherents. The study notes a shift from a one-size-fits-all religious education approach toward an inclusive curriculum that incorporates different religious education curriculum models, fostering mutual respect among students of different faiths. This transition suggests several curriculum reform strategies: how educators, curriculum developers, and stakeholders can collaborate to design an environment that values diversity and enables positive engagement among students from various backgrounds. Keyword: Islamic Religious Education, Curriculum, Multiculturalism, and Pluralism